Unsilencing Sexual Torture: Responses to Refugees and Asylum Seekers in Denmark - Canning, Victoria (2016)
Debates around torture have proliferated in the past decade, placing the topic more centrally in criminological studies and research. However, the ways in which torture is recognized or responded to often pivot on narrow legalistic definitions which do not necessarily incorporate the gendered nature of torturous violence, and in particular sexual torture. In developing a regional case study focussed on Denmark, this article critically addresses the ways in which sexual torture is silenced in terms of state and organizational responses to survivors. Additionally, the increasingly punitive ways in which states respond to asylum seekers more generally means that impacts of torture, sexual torture and persecution can be compounded by structural conditions which ultimately exacerbate social, emotional, physical and psychological effects of violence